Patient‐derived xenograft model in colorectal cancer basic and translational research. Issue 1 (21st December 2022) - Liu, Xiaofeng; Xin, Zechang; Wang, Kun
Abstract: Colorectal cancer (CRC) is one of the most popular malignancies globally, with 930 000 deaths in 2020. The evaluation of CRC‐related pathogenesis and the discovery of potential therapeutic targets will be meaningful and helpful for improving CRC treatment. With huge efforts made in past decades, the systematic treatment regimens have been applied to improve the prognosis of CRC patients. However, the sensitivity of CRC to chemotherapy and targeted therapy is different from person to person, which is an important cause of treatment failure. The emergence of patient‐derived xenograft (PDX) models shows great potential to alleviate the straits. PDX models possess similar genetic and pathological characteristics as the features of primary tumors. Moreover, PDX has the ability to mimic the tumor microenvironment of the original tumor. Thus, the PDX model is an important tool to screen precise drugs for individualized treatment, seek predictive biomarkers for prognosis supervision, and evaluate the unknown mechanism in basic research. This paper reviews the recent advances in constructed methods and applications of the CRC PDX model, aiming to provide new knowledge for CRC basic research and therapeutics. Abstract : The establishment of PDX bio‐bank for precision medicine. Specimens from CRC patients enrolled in the study are submitted to PDX bio‐bank. Researchers can take advantages of the bio‐banks to screen drugs, uncover biomarkers, and study the basic mechanisms. The latent drugs will submit to animal tests using PDX in bio‐banks. The effective drugs and biomarkers will improve therapeutic effects.